The Authority Relationship Of Central And Local Governments In Forming Laws And Regulations: Between Indonesia And Malaysia - Aan Eko Widiarto; Muhamad Sayuti Hassan; Mohd Hazmi Mohd Rusli; Endrianto Bayu Setiawan (Fakultas Hukum Universitas Muhammadiyah Malang, 2025)
INdex (Tier 2)